An idealized study of near equatorial river plumes - Palma, Elbio Daniel (2017)
The dynamics of near equatorial river plumes (NERPs) are investigated using a highly idealized model. The spreading of a NERP from an eastern boundary is characterized by a continuous shedding of westward propagating eddies. This process transfers the bulk of the freshwater discharge to the deep ocean, thus distinguishing NERPs from their midlatitude counterparts. In the long-term limit, a NERP can be rationalized as a β-plume emanating from a coastal source. The evolution of NERPs in an unstratified basin is quite different from that in a stratified one. The spin-up in an unstratified basin is characterized by the formation of an anticyclonic bulge, which spreads westward thus creating a density stratification that favors the subsequent development of smaller and faster moving secondary eddies. The collision of the secondary eddies with the leading bulge arrests the effects of mixing thus allowing the further spreading of the buoyancy anomaly. In a stratified basin, the generation of anticyclonic eddies is accompanied by a concurrent generation of cyclones, which pump saltier waters to the surface hence leading to smaller sea surface salinity (SSS) anomalies. NERPs are sensitive to variations of the freshwater flux (Qfw) and the geomorphological setting. Larger Qfw generates bigger eddies, which spread at a rate proportional to the square root of the normalized flux. Wide shelves allow the interaction of the eddies with the bottom, thus promoting a cyclonic shift of the axis of the eddy train. The inclination of the coast affects the dynamical balance controlling the near-field behavior of NERPs.